Phenotypic Characterization of Non-toxigenic Clostridioides difficile Strains Isolated From Patients in Mexico - Camorlinga, Margarita; Sanchez-Rojas, Michelle; Torres, Javier; Romo-Castillo, Mariana (Frontiers in Microbiology, 2019)
Clostridioides difficile is a Gram positive, sporulated, rod-shape, anaerobic pathogen responsible for nosocomial diarrhea and colitis, mainly in antibiotic treated patients. C. difficile produce two toxins responsible for disease, toxin A (TcdA) and toxin B (TcdB), although not all strains produce them. Non-toxigenic C. difficile (NTCD) strains are able to colonize the intestinal mucosa and are often isolated from asymptomatic individuals. NTCD are poorly studied, their evolutionary history has not been elucidated, and their relationship with illness remains controversial. The aim of this work was to analyze the phenotype of NTCD strains isolated from clinical cases in hospitals of México, and whether NTCD strains present characteristics that differentiate them from the toxigenic strains. Seventy-four C. difficile strains isolated from patients were tested for cytotoxicity and 14 were identified as NTCD strains. We analyzed phenotypical characteristics that are important for the biology of C. difficile like colony morphology, antibiotic resistance, motility, sporulation and adherence. Strains were also genotyped to determine the presence of genes coding for TcdA, TcdB and binary toxin and ribotyped for 027 type. When compared with toxigenic strains, NTCD strains presented an enlarged branched colony morphology, higher resistance to metronidazole, and increased sporulation efficiency. This phenotype has been reported associated with mutations that regulates phenotypic characteristics like swimming, sporulation or adhesion. Our results show that phenotype of NTCD strains is heterogeneous but still present characteristics that differentiate them from toxigenic strains.